2018
DOI: 10.5465/ambpp.2018.13955abstract
|View full text |Cite
|
Sign up to set email alerts
|

No Expectation, No Disappointment: How Does Meta-Accuracy Affect Hireability?

Abstract: People may or not know the impression they convey to others (meta-accuracy). However, little research has addressed to what extent meta-accuracy affects social outcomes such as hireability (recruiter's intention to hire). Three studies were conducted to test whether people who knew the impression they conveyed are the ones who are more likely to get hired. Results of polynomial regression and responses surface analyses showed that meta-accuracy was related to hireability, whether meta-accuracy concerns skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…They also tend to over-estimate how easy it is for a listener to understand them when communicating ambiguous sentences (Keysar & Henly, 2002). Research has shown that such over-estimation can lead to negative outcomes, such that individuals who over-estimate the impression they convey to recruiters during a job interview are perceived as less hireable than those who under-estimate the impression they convey (Renier, Kleinlogel, Toma, Schmid Mast, & Murphy, 2018).…”
Section: Meta-perception and Its Accuracymentioning
confidence: 99%
“…They also tend to over-estimate how easy it is for a listener to understand them when communicating ambiguous sentences (Keysar & Henly, 2002). Research has shown that such over-estimation can lead to negative outcomes, such that individuals who over-estimate the impression they convey to recruiters during a job interview are perceived as less hireable than those who under-estimate the impression they convey (Renier, Kleinlogel, Toma, Schmid Mast, & Murphy, 2018).…”
Section: Meta-perception and Its Accuracymentioning
confidence: 99%
“…This insight, called meta-accuracy , is defined as the correspondence between a person’s perceptions (e.g., Paul’s impression of Mia) and that person’s metaperceptions of these perceptions (e.g., Mia’s perception of Paul’s impression of Mia). Meta-accuracy is believed to be a critical interpersonal skill (Carlson & Elsaadawy, 2021), a central component of adjustment (Carlson, 2016a), and associated with a range of beneficial correlates (Brion et al, 2015; Carlson, 2016b; Carlson & Oltmanns, 2018; Renier et al, 2018). It is therefore important to understand and identify individual differences in being a good metaperceiver: To what degree do individuals differ in meta-accuracy, how do metaperceivers achieve being more accurate than others and who is especially good at it?…”
Section: Does the Good Metaperceiver Exist?mentioning
confidence: 99%
“…This insight, called meta-accuracy, is defined as the correspondence between a person's perceptions (e.g., Paul's impression of Mia) and that person's meta-perceptions of these perceptions (e.g., Mia's perception of Paul's impression of Mia). Meta-accuracy is believed to be a critical interpersonal skill (Carlson & Elsaadawy, 2019), a central component of adjustment (Carlson, 2016a), and associated with a range of beneficial correlates (Brion et al, 2015;Carlson, 2016b;Carlson & Oltmanns, 2018;Renier et al, 2018). It is therefore important to understand and identify individual differences in being a good meta-perceiver: To what degree do individuals differ in meta-accuracy, how do meta-perceivers achieve being more accurate than others and who is especially good at it?…”
Section: Using the Social Meta-accuracy Modelmentioning
confidence: 99%